Tantangan Dan Strategi Manajemen Sumber Daya Manusia Dalam Menghadapi Fenomena Great Resignation - Fajariah Asmawati; Kriara Latifah Dinar; Sri Sundari; Marisi Pakpahan (Jurnal Cakrawala Akademika, 2024)
The Great Resignation phenomenon that has occurred since the COVID-19 pandemic has posed significant challenges for organizations in managing human resources (HR). The high employee turnover rate is due to a variety of factors, such as job dissatisfaction, burnout, increasing demand for work-life balance, and opportunities in a more competitive labor market. This research aims to identify the main challenges faced by organizations and the strategies that have been implemented to overcome this phenomenon. Through a qualitative descriptive approach based on literature studies, this study finds that the implementation of a hybrid work system, improving employee welfare, and promoting employee engagement are effective strategies in reducing turnover. Global case studies show that organizations that are able to respond quickly to the demands of flexibility and employee well-being tend to be more successful in retaining their talent. This research contributes to the HR management literature by strengthening the relevance of work flexibility and employee well-being policies in the context of global crises.